Weighted Central BMO Spaces and Their Applications - Huan Zhao; Zongguang Liu (Journal of Function Spaces)
In this paper, the central BMO spaces with Muckenhoupt Ap weight is introduced. As an application, we characterize these spaces by the boundedness of commutators of Hardy operator and its dual operator on weighted Lebesgue spaces. The boundedness of vector-valued commutators on weighted Herz spaces is also considered.